Giant dielectric phenomenon of Ba0.5Sr0.5TiO3/CaCu3Ti4O12 multilayers due to interfacial polarization for capacitor applications. Issue 4 (April 2019) - Zhao, Lili; Xu, Ruoxin; Wei, Yuxing; Han, Xiao; Zhai, Chunxue; Zhang, Zhixiang; Qi, Xiaofei; Cui, Bin; Jones, Jacob L.
Abstract: Ba0.5 Sr0.5 TiO3 /CaCu3 Ti4 O12 (BST/CCTO) multilayers with different stack sequences were deposited on LaNiO3 (LNO)/SiO2 /Si substrates by a sol-gel process. The dielectric properties of BST/CCTO multilayers are significantly affected by the deposition sequence, the layer thickness and the impurities, effects that are interpreted using the Maxwell-Wagner interfacial polarization model. Impurities are generated by elemental interdiffusion at the interfaces of BST/CCTO, and less at the interfaces of BST/LNO and CCTO/LNO. The dielectric permittivity of the CCTO/BST/LNO/SiO2 /Si sample reaches 352, 200 at 10 kHz, and stabilizes above 20, 000 in the range of 100 kHz to 1 MHz. This work demonstrates an effective approach to enhance dielectric properties for film capacitor applications by constructing multilayers with specific deposition sequences and layer thicknesses.